2004
DOI: 10.1002/anie.200353436
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Selective Olefin Hydrogenation by a Pd Nanocluster Provided in an Apo‐Ferritin Cage

Abstract: Deep penetration by substrates through the size‐restricted channels of an apo‐ferritin cage results in size‐selective olefin hydrogenation at the Pd nanocluster core (see picture). The encapsulated zero‐valent cluster is synthesized in situ by chemical reduction of PdII ions in the apo‐ferritin cage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
231
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(242 citation statements)
references
References 25 publications
3
231
0
Order By: Relevance
“…It was shown that the catalytic system discriminates with respect to size of the substrates, via the 3-fold channels that cross the protein cage ( Figure 34). 318 Alteration of the outer surface of ferritin has been investigated by Mann and co-workers. Alkylated derivatives of ferritin were prepared by carbodiimideactivated coupling of long chain primary amines to carboxylic acid residues on the protein surface.…”
Section: Ferritinmentioning
confidence: 99%
“…It was shown that the catalytic system discriminates with respect to size of the substrates, via the 3-fold channels that cross the protein cage ( Figure 34). 318 Alteration of the outer surface of ferritin has been investigated by Mann and co-workers. Alkylated derivatives of ferritin were prepared by carbodiimideactivated coupling of long chain primary amines to carboxylic acid residues on the protein surface.…”
Section: Ferritinmentioning
confidence: 99%
“…A synthesis of ferrimagnetic ferritin (γ-Fe 2 O 3 ) was achieved by a chemical remineralization procedure [7,8] with the assistance of H 2 O 2 oxidant in 3-[(1,1-dimethyl-2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid(AMPSO) buffer (pH 8.5) at 65 o C under N 2 gas. Biomineralization of other metals (i.e., Co [9,11], Mn [12][13][14], Ni [15], and Pd [16]), semiconductors (CdS) [17], and metal-oxo-anions composites [18] into the ferritin cavity has also been reported. Wong et al demonstrated the magnetic transition from superparamagnetic to ferromagnetic CoPt cored ferritin [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These properties can be achieved not only by using the nanoreactor route but also by using apoferritin shell reassembly in the presence of target NPs [63]. [53,65,[70][71][72][73]. The scheme of NP synthesis using apoferritin is presented in Figure 3.…”
Section: Synthesis Of Nanoparticles Within the Apoferritin Cagementioning
confidence: 99%